(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
In the present work use of Beta-Cyclodextrin for inclusion of Carvedilol, an antihypertensive drug with poor solubility and high first pass metabolism was studied, in order to improve its dissolution rate. The complex prepared by kneading method was characterized by Differential Scanning Calorimetry, Fourier Transformation Infra Red Spectroscopy and X-Ray Diffractometry along with the plain drug and physical mixture. The drug so complexed was incorporated into a buccal dosage form to by pass first pass metabolism to improve its bioavailability. The buccal tablets containing complex showed reasonable mucoadhesive strength. The dissolution and permeability across pig buccal mucosa were improved in case of tablets containing the complex as compared to plain drug tablet. Key words: Carvedilol; Beta-Cyclodextrin; Complexation; Dissolution; Characterization; Permeation. DOI: 10.3329/bjsir.v45i2.5709 Bangladesh J. Sci. Ind. Res. 45(2), 123-128, 2010